ASSESSMENT OF KNOWLEDGE AND BARRIERS IN SEXUAL AND REPRODUCTIVE HISTORY TAKING BY RESIDENTS IN A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Background: Sexual history taking plays a pivotal role in medical history taking and examination and ensures complete medical evaluation. Doctors need to be comfortable in asking questions related to a patient’s sexual health in order to explore and identify the sexual problems faced by their patients so they can counsel and manage their patients accordingly.Objective: For the assessment of knowledge and barriers in obtaining sexual and reproductive history by resident’s doctors in tertiary care hospitals.Study Design: A cross-sectional study.Study Setting: Study was conducted at Central Park Teaching Hospital Lahore.Study Duration: From May 2024 to September 2024.Materials and Methods: In this study, all the resident doctors including house officers, postgraduate residents, and clinical faculty will be included in the study by employing non-random convenient sampling technique. For the assessment of knowledge and barriers regarding sexual and reproductive health; a 20 questions-based questionnaire was designed based on likert scale from disagree, neutral to agree was employed.Results: Approximately 80.3% and 60.6% of physicians indicated that cultural and religious disparities are obstacles in addressing sexual health issues with patients.  The designation was statistically significant, indicating that cultural differences were perceived as a barrier to discussing sexual health issues with patients.Conclusion: The importance of training and the practice of the sexual history-taking technique cannot be underscored, but there are still important barriers at play a key message arising from this research is that it is imperative that educators include structured, practical training on sexual history taking in medical training.